Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1086/500185
|View full text |Cite
|
Sign up to set email alerts
|

Spectropolarimetric Investigation of the Propagation of Magnetoacoustic Waves and Shock Formation in Sunspot Atmospheres

Abstract: Velocity oscillations in sunspot umbrae have been measured simultaneously in two spectral lines: the photospheric Silicon i 10827Å line and the chromospheric Helium i 10830Å multiplet. From the full Stokes inversion of temporal series of spectropolarimetric observations we retrieved, among other parameters, the line of sight velocity temporal variations at photospheric and chromospheric heights. Chromospheric velocity oscillations show a three minute period with a clear sawtooth shape typical of propagating sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
244
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(277 citation statements)
references
References 25 publications
29
244
4
Order By: Relevance
“…One of these is umbral flashes (UFs), sudden brightenings that are observed in the core of the chromospheric Ca ii lines with a periodicity of about 3 min (Wittmann 1969). Umbral flashes are a result of waves propagating from the photosphere which turn into shocks on reaching the less dense chromosphere and are seen as blueshifted emission reversals in the core of the Ca ii 8542 Å line (Rouppe van der Voort et al Centeno et al 2006;Felipe et al 2010). Although UFs are a large-scale phenomenon, it has been shown that within a resolution element there are at least two distinct magnetic components, one that has the same polarity as the spot with zero or slightly downflowing velocity, while the other is related to the shock wave that has a line core emission reversal and strong upflows (Socas-Navarro et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One of these is umbral flashes (UFs), sudden brightenings that are observed in the core of the chromospheric Ca ii lines with a periodicity of about 3 min (Wittmann 1969). Umbral flashes are a result of waves propagating from the photosphere which turn into shocks on reaching the less dense chromosphere and are seen as blueshifted emission reversals in the core of the Ca ii 8542 Å line (Rouppe van der Voort et al Centeno et al 2006;Felipe et al 2010). Although UFs are a large-scale phenomenon, it has been shown that within a resolution element there are at least two distinct magnetic components, one that has the same polarity as the spot with zero or slightly downflowing velocity, while the other is related to the shock wave that has a line core emission reversal and strong upflows (Socas-Navarro et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Yet another alternative explanation for the lowered acoustic cutoff frequency involves radiative cooling. A loose reasoning can be made where the more inhomogeneous plage region has a shorter radiative cooling time which in turn leads to a decreased acoustic cutoff frequency (Centeno et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These shocks steepen from the three-minute oscillations, observed at the discovery of umbral flashes themselves (Beckers & Tallant 1969) as well as in early follow-up papers (Wittmann 1969). In turn, the threeminute oscillations are likely caused by a resonance in the umbral atmosphere itself (see early review by Thomas 1985) and are, at least partially, powered by the photospheric five-minute oscillations (Centeno et al 2006).…”
Section: Introductionmentioning
confidence: 86%